'Whole onflow', the productive event: an articulation through health. (November 2020) - Andrews, Gavin J.; Duff, Cameron
Abstract: In this paper we develop an understanding of 'whole onflow'. Extending philosopher Ralph Pred's original descriptions in materialist directions consistent with posthumanist and non-representational theory, we treat whole onflow as the progressing moment ever-materializing; as a never-ending more-than-human event happening everywhere that is existed in, registered, malleable and productive. In particular, using examples in health, we describe whole onflow's core qualities that lend it, as a vital forceful becoming, its productive capacities. We argue that whole onflow offers compelling ways of understanding the processual origins of health and many productions besides in all their diversity. Moreover, we argue that it offers ways of understanding how humans figure as part of the Universe's becoming. Highlights: Describes the universal event of whole onflow. Whole onflow - the progressing moment ever-materializing, ever-breaking wave of life. Articulates, using health as an empirical example, whole onflow's productive capacities. Articulates whole onflow's core qualities and some ways it might be studied.